Ex‐military Personnel in the Criminal Justice System: A Cross‐sectional Study. (15th July 2013) - Bray, Isabelle; O'Malley, Paula; Ashcroft, Sarah; Adedeji, Liz; Spriggs, Adam
Abstract: The aim of this article is to estimate the proportion of Regular veterans in England and Wales who are in prison or supervised by a Probation Trust. A cross‐sectional data linkage approach was taken, matching a database of Service leavers with prison and probation data. The proportion of those in the criminal justice system who are veterans was estimated to be 3.4%. For men aged 18–54 years, the proportion of the general population in prison was 43% (95% CI: 37%–49%) higher than the proportion of veterans in prison. There is no evidence that veterans are over‐represented in the criminal justice system.